From Policy to Practice: Strategies to Meet Physical Activity Standards in YMCA Afterschool Programs - Beets, Michael W. (2014)
BACKGROUND: In 2011, the U.S. YMCA adopted activity standards recommending that afterschool programs (ASPs) ensure all children engage in a minimum of 30 minutes of moderate to vigorous physical activity (MVPA) daily during the ASP. ASPs decide how to accomplish this standard, for which few effective strategies exist. PURPOSE: To evaluate strategies designed to help ASPs meet the MVPA standard. DESIGN: Single group intervention with pretest and three follow-up measures repeated-cross-sectional design with a subsample cohort. SETTING/PARTICIPANTS: Four large-scale YMCA ASPs, serving approximately 500 children each day. INTERVENTION: Community-based participatory development of strategies focused on modification of program schedules, professional development training, and weekly checklists to evaluate activity opportunities. MAIN OUTCOME MEASURES: Accelerometry-derived MVPA classified as meet or fail-to-meet the 30min/d MVPA standard collected over a minimum of four nonconsecutive days at baseline (fall 2011) and 3 follow-up assessments (spring 2011, fall 2012, spring 2013). Random intercept logistic regression models evaluated the probability of meeting the standard for boys and girls, separately (analyzed summer 2013). RESULTS: A total of 895 children (aged 5–12 years, 48.4% girls) representing 3,654 daily measures were collected across the four assessments. The percentage of girls and boys meeting the MVPA standard at baseline was 13.3% and 28.0%, respectively. By spring 2013 this increased to 29.3% and 49.6%. These changes represented an increase in the odds of meeting the 30min MVPA/d standard by 1.5 (95CI 1.1 to 2.0) and 2.4 (95CI 1.2 to 4.8) for girls and boys, respectively. CONCLUSIONS: The strategies developed herein represent an effective approach to enhancing current practice within YMCA ASPs to achieve existing MVPA standards. Additional work is necessary to identify the cost associated with using the strategies, as well as to evaluate the scalability of the strategies in a larger sample of ASPs.